Morphometric characteristics of caudal cranial nerves at petroclival region in fetuses - ÖZKAN, MAZHAR; ÖZDOĞMUŞ, NECMETTİN ÖMER; YILDIZ, SERCAN DOĞUKAN; ŞEHİRLİ, ÜMİT SÜLEYMAN; VERİMLİ, URAL (SPRINGER, 2016)
Morphometric measurements of cranial nerves in posterior cranial fossa of fetus cadavers were carried out in an attempt to identify any asymmetry in their openings into the cranium. Twenty-two fetus cadavers (8 females, 14 males) with gestational age ranging between 22 and 38 weeks (mean 30 weeks) were included in this study. The calvaria were removed, the brains were lifted, and the cranial nerves were identified. The distance of each cranial nerve opening to midline and the distances between different cranial nerve openings were measured on the left and right side and compared. The mean clivus length and width were 21.2 +/- A 4.4 and 13.2 +/- A 1.5 mm, respectively. The distance of the twelfth cranial nerve opening from midline was shorter on the right side when compared with the left side (6.6 +/- A 1.1 versus 7.1 +/- A 0.8 mm, p = 0.038). Openings of other cranial nerves did not show such asymmetry with regard to their distance from midline, and the distances between different cranial nerves were similar on the left and right side. Cranial nerves at petroclival region seem to show minimal asymmetry in fetuses.
Keywords: Caudal cranial nerves; Clivus; Fetus; Morphometry; Petroclival region; ANATOMY